Age-Related Progression of Degenerative Lumbar Kyphoscoliosis: A Retrospective Study - Ishihara, Yohei (Spine Surg Relat Res, 2020)
INTRODUCTION: Degenerative lumbar kyphoscoliosis is a serious clinical condition that affects activities of daily living. This study aimed to investigate the age-related progression of nonoperative degenerative lumbar kyphoscoliosis, to clarify its final state in elderly people, and to identify factors associated with its progression. METHODS: This retrospective longitudinal study included 115 nonoperative cases (mean age at first consultation, 70.9 years; range, 50-89 years). All were followed up for >6 years. The analysis included changes between initial and latest measurements in the coronal parameters (Cobb angle, L4 tilt angle, intervertebral angle, lateral spondylolisthesis, and C7-central sacral vertical line) and sagittal parameters (thoracic kyphosis, lumbar lordosis, pelvic incidence, pelvic tilt, sacral slope, sagittal vertical axis, and vertebral wedging rate). Factors in scoliosis progression were investigated by analyzing the correlations between the initial parameter values and the increase in Cobb angle. RESULTS: Changes in the coronal parameters increased with age from 50s to 70s but decreased significantly in those aged 80s. Sagittal parameters increased by the age group, accelerating in those aged 80s, with the progression of vertebral wedging. In patients aged 50s-70s, the increase in Cobb angle correlated significantly with the initial Cobb angle, L4 tilt angle, and L4/L5 intervertebral angle. However, in the cases without initial scoliosis, the increase in Cobb angle correlated significantly only with the L4 tilt angle. There were no significant differences in any parameter according to the use of a trunk brace or medication for osteoporosis. CONCLUSIONS: L4 tilt angle is an important factor in the progression of degenerative scoliosis. The progression of scoliosis gradually ends after the age of 80 years with the decreasing variation of L4 tilt angle, whereas kyphosis accelerates with aging, especially in those aged >80 years, with the progression of vertebral wedging.